Oral invasive procedures in Glanzmann thrombasthenia: a retrospective observational study - Maxime Delarue; François Severac; Martine Soell; Léa Pierre; Dominique Desprez; Bornert Fabien (Research and Practice in Thrombosis and Haemostasis)
Background: Glanzmann thrombasthenia (GT) is a very rare autosomal inherited bleeding disease affecting megakaryocyte lineage with impacts on oral health such as gingival bleeding, which requires specific management protocols. Very few clinical cases have been published in the dental and hematologic literature. Objectives: This study focuses on a series of 21 patients affected specifically by GT and their hemorrhagic prophylaxis management with the use of recombinant activated factor VII (rFVIIa) for dental extractions and full-mouth debridement. Methods: Data were collected from medical and dental records. rFVIIa was administered prophylactically for oral procedures, following a standardized protocol. Each sessions were performed by experienced oral surgeons, and outcomes were analyzed with a focus on bleeding complications and adverse events. Results: Forty-one full-mouth debridements and 176 dental extractions were performed during 102 sessions of dental care in an outpatient setting. A total of 226 injections of rFVIIa was delivered. The mean number of injections was 2.2 (range, 1-4) per dental procedure. The overall rate of bleeding complications was 5.9% (n = 6). All 6 hemorrhagic complications were classified as minor bleeding. No thromboembolic event or allergic reaction was observed. Conclusion: The data presented in this retrospective observational study support the efficacy and safety of rFVIIa for the prevention of bleeding during invasive dental procedures in patients affected by GT. The rFVIIa protocol presented here seems to be a safe and efficient protocol for the prevention of bleeding during invasive oral procedures.